Connected seniors: how older adults in East York exchange social support online and offline - Quan-Haase, Anabel; Mo, Guang Ying; Wellman, Barry (Information, communication & society, 2017)
How do older adults mobilize social support, with and without digital media? To investigate this, we focus on older adults 65+ residing in the Toronto locality of East York, using 42 interviews lasting about 90 minutes done in 2013-2014. We find that digital media help in mobilizing social support as well as maintaining and strengthening existing relationships with geographically near and distant contacts. This is especially important for those individuals (and their network members) who have limited mobility. Once older adults start using digital media, they become routinely incorporated into their lives, used in conjunction with the telephone to maintain existing relationships but not to develop new ones. Contradicting fears that digital media are inadequate for meaningful relational contact, we found that these older adults considered social support exchanged via digital media to be real support that cannot be dismissed as token. Older adults especially used and valued digital media for companionship. They also used them for coordination, maintaining ties, and casual conversations. Email was used more with friends than relatives; some Skype was used with close family ties. Our research suggests that policy efforts need to emphasize the strengthening of existing networks rather than the establishment of interventions that are outside of older adults' existing ties. Our findings also show that learning how to master technology is in itself a form of social support that provides opportunities to strengthen the networks of older adults.